Clinical and Functional Outcome of Acetabular Fracture Fixation: 5-year follow up Retrospective Cohort Study (Journal of Pakistan Orthopaedic Association, 2024)
Objective: Acetabular fractures are amongst complex injuries that Orthopaedic surgeons manage. Commonest cause of these fractures are high-energy trauma, and are frequently accompanied by additional possible life threatening injuries. If not addressed appropriately, Acetabular fractures may result in early hip osteoarthritis. This study was carried out to assess clinical and functional outcomes of acetabulum fracture fixation at 5 years’ follow-up, using Harris hip score.Methods: This retrospective study was done at Liaquat National Hospital from 2010 to 2022, which included 173 patients who underwent acetabular fracture fixation. After excluding patients who expired, did not respond or were lost to follow-up, final sample size summed up to 72 patients. Data encompassed patient demographics, injury mechanisms, treatment details, and complications. Fracture patterns were classified per Letournel and Judet criteria. Surgical intervention involved acetabulum open reduction and internal fixation (ORIF) by a single surgeon who is specialized in pelvic and acetabulum surgeries. Protocols for postoperative rehabilitation and thromboprophylaxis were followed. Clinical and functional outcome was assessed using HHS at five-year follow-up.Results: This study group included 72 patients with a mean age of 45.36 ± 16.3 years and included 64 men and 8 women. Road traffic accidents was the leading cause of acetabular fractures (79.2%), with solitary acetabular fractures accounting for the majority of cases (87.5%). Fracture classification revealed anterior column fractures as the most common subtype (66.7%). The mean HHS at the five-year follow-up was 90.78, indicating excellent outcomes in the majority (68%) of patients. 2 patients (2.8%) developed avascular necrosis, and limb length discrepancy was seen in 6 patients (8.3%).Conclusion: This study underscores the complexity of acetabular fractures and highlights the favorable outcomes of surgical intervention using the Harris Hip Score. Complications like avascular necrosis and limb length discrepancy require regular follow-ups and management accordingly. While acknowledging study limitations, including its retrospective nature and sample size, this research showed excellent clinical and functional outcome after acetabular fracture fixation.